Causal relationship occupation injurj in the food industries - Evtushenko, Olga; Evtushenko, Oleg (My University, 2013)
The presented article is devoted to the results of research of technical and organizational reasons and types of events that occur during injuries at the food enterprises. Obtained risk matrices of the injuries with death or deathless consequences for 15 types of accidents that were causing to accidents, and 16 reasons of traumatism during 2003–11 period. There are quantitative statistical evaluations for 240 types of risk reasons for binary groups “the reason of an accident – type of traumatic effect” in the matrices of risk. The presence of quantitative evaluations in the matrices of risk permits to provide ranking of risk types in accordance to their seriousness. Such measure makes choosing of preventive methods much easier and provides effective influence onto total risks (at the expense of orientation of prophylaxis in accordance to types with the highest rate of risk).The main feature of risk matrices is that the comparison of two matrices (for traumatism with death and deathless consequences) gives a chance to get additional characteristic about seriousness of traumatism. This information can be expressed through the quantity of victims in accidents without death consequences relatively to one death accident. It is the first time the regularity of the ranking of binary ratio “the reason of an accident – type of traumatic effect” is set for enterprises of the food industry. And its main clue is that approximately 20% of them causes 75% of the traumatism risk.
Keywords: causal relationships; accidents; injuries; production traumatism; причинно-наслідкові зв’язки; нещасний випадок; виробничий травматизм; виробнича травма; кафедра екології та екоменеджменту